2021
DOI: 10.1186/s43161-021-00049-5
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of cough assist device on blood gasses and period of mechanical ventilator for pneumonic children with general hypotonia

Abstract: Background Cough assist devices play an important role with patients in the intensive care unit (ICU), particularly those with neuromuscular diseases which had abnormal muscle tone. It was previously thought to be the main technique for improving cough efficacy, which aids in weaning from mechanical ventilation and improves patient outcomes. So, we selected randomly the odd numbers from Abo El-Reesh hospital records, and 30 children of both sexes with pneumonia were selected, aged from 6 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Author details 1 Cairo University Specialized Pediatric Hospital (CUSPH), Cairo, Egypt. 2 Faculty of Physical Therapy, Cairo University, Cairo, Egypt.…”
Section: Open Access Of Faculty Of Physical Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Author details 1 Cairo University Specialized Pediatric Hospital (CUSPH), Cairo, Egypt. 2 Faculty of Physical Therapy, Cairo University, Cairo, Egypt.…”
Section: Open Access Of Faculty Of Physical Therapymentioning
confidence: 99%
“…Following the publication of the original article [1], the authors identified an error in the sequence of the authors.…”
mentioning
confidence: 99%